Peningkatan Usaha Beternak Ayam Petelur pada Kelompok Peternak Unggas Dusun Tukak Bendu Santong Mulia Kayangan Kabupaten Lombok Utara - Dwi Kusuma Purnamasari; Syamsuhaidi Syamsuhaidi; K.G. Wiryawan; Erwan Erwan; Sumiati Sumiati; Pardi Pardi; Tjok S. Binetra (Universitas Mataram, 2021)
The productivity of laying hens in North Lombok Regency has not yet reached its maximum. Egg production has not been able to supply the needs of the people, hotels and restaurans in North Lombok Regency. Assistance activities from various parties are needed in order to improve the business of laying hens through the share of science, technology, and training in livestock. The community service activity was initiated by a speech from the head of the breeders group who revealed the various problems by breeders in improving their poultry farming business. The next activity was the share knowledge of community service which include successful management of laying hens, techniques for preparing various feed formulas by utilizing and techmiques for improving the quality of alternative feeds. The community service activity was attended by 35 breeders and the discussion was active. The breeders who attended were farmers who are members of the ‘Gemas’ Layer Farmer Group Associantion, which has 23 members with a business capacity of 20.000 layer hens. The farmer group is eager to increase egg production in order the needs of hotels, restaurants, people in North Lombok Regency. Through the use of alternative feeds by arranging variouse feed formulas according to the needs of liverstock is a solution that can be applied to increase the quantity and quality of eggs. complete feed; alternative feed; quantity; quality; egg